Strict monotonicity and unique continuation of the biharmonic operator - Najib Tsouli (Boletim da Sociedade Paranaense de Matemática, 2012)
In this paper, we will show that the strict monotonicity of the eigenvalues of the biharmonic operator holds if and only if some unique continuation property is satisfied by the corresponding eigenfunctions.